Area-based approaches and urban recovery in the Pacific: lessons from Fiji, Solomon Islands and Vanuatu. (April 2022) - Keen, Meg; Sanderson, David; Osborne, Kira; Deo, Roshika; Faith, Janet; Ride, Anouk
Flooding events are set to worsen in rapidly urbanising Pacific Islands. (1) Most Pacific Island cities and towns are in low-lying areas vulnerable to more severe tropical cyclones and rising sea levels. Approaches to disaster response and recovery need to improve. This article uses four principles drawn from area-based approaches (ABAs) – people-centred responses, adaptive processes, multi-sector collaboration and reflective practice – to review urban disaster recovery efforts in Fiji, Solomon Islands and Vanuatu. Information was gathered through key informant interviews and a literature review. The research found positive examples of collaboration, locally tailored social protection mechanisms and community leadership. It also found challenges, including bypassed community structures and traditional adaptation techniques, duplication of efforts and weak coordination. The article concludes with a call to localise ABA approaches further, to strengthen people-centred disaster recovery and locally owned resilience.